Recalcitrance to transformation, a hindrance for genome editing of legumes - Nivya, V. M.; Shah, Jasmine M. (Frontiers in Genome Editing, 2023)
Plant genome editing, a recently discovered method for targeted mutagenesis, has emerged as a promising tool for crop improvement and gene function research. Many genome-edited plants, such as rice, wheat, and tomato, have emerged over the last decade. As the preliminary steps in the procedure for genome editing involve genetic transformation, amenability to genome editing depends on the efficiency of genetic engineering. Hence, there are numerous reports on the aforementioned crops because they are transformed with relative ease. Legume crops are rich in protein and, thus, are a favored source of plant proteins for the human diet in most countries. However, legume cultivation often succumbs to various biotic/abiotic threats, thereby leading to high yield loss. Furthermore, certain legumes like peanuts possess allergens, and these need to be eliminated as these deprive many people from gaining the benefits of such crops. Further genetic variations are limited in certain legumes. Genome editing has the potential to offer solutions to not only combat biotic/abiotic stress but also generate desirable knock-outs and genetic variants. However, excluding soybean, alfalfa, and Lotus japonicus, reports obtained on genome editing of other legume crops are less. This is because, excluding the aforementioned three legume crops, the transformation efficiency of most legumes is found to be very low. Obtaining a higher number of genome-edited events is desirable as it offers the option to genotypically/phenotypically select the best candidate, without the baggage of off-target mutations. Eliminating the barriers to genetic engineering would directly help in increasing genome-editing rates. Thus, this review aims to compare various legumes for their transformation, editing, and regeneration efficiencies and discusses various solutions available for increasing transformation and genome-editing rates in legumes.